Нове місцезнаходження Ophrys apifera Huds. (Orchidaceae) в Україні - Данилик, І.М.; Борсукевич, Л.М. (Український ботанічний журнал, 2011)
Приводятся сведения о новом местонахождении редкого вида флоры Украины — Ophrys apifera Huds (Orchidaceae Juss.). Оно было обнаружено летом 2010 г. на территории Рогатынского Ополья (Западное Подолье) в окресностях с. Водники Галицкого р-на Ивано-Франковской обл. Даны номенклатурная цитата вида, сведения о его географическом распространении и эколого-ценотических особенностях местопроизрастания на северо-восточной границе ареала. Сделано предположение о миграционном пути O. apifera и реликтовости обнаруженного местонахождения. A new locality for rare orchid species Ophrys apifera Huds. (Orchidaceae Juss.) is reported. It was discovered on the territory of Rogatynske Opillya (Western Podillya), near Vodnyky village, Ivano-Frankivsk Region, in summer 2010. Relevant nomenclatural citations for the species are provided. Information about its geographical distribution and ecological-coenotic features of the locality at the northeastern border of the range are given. It is regarded as a relic locality. Migration pathways for O. apifera are suggested.